Reducing the impact of carbapenem-resistant Enterobacteriaceae on vulnerable patient groups: what can be done?. Issue 6 (December 2016) - Metan, Gökhan; Akova, Murat
Abstract : Purpose of review: Carbapenem-resistant Enterobacteriaceae (CRE) is a worldwide challenge and associated with a high mortality rate in critically ill patients. This review focused on rapid diagnosis, optimization of antimicrobial therapy, and implication of effective infection control precautions to reduce impact of CRE on vulnerable patients. Recent findings: Several new diagnostic assays have recently been described for the early diagnosis of CRE. Retrospective studies are supportive for colistin plus meropenem combination for the treatment of CRE infections; however, solid evidence is still lacking. Ceftazidime–avibactam may be an effective therapeutic agent for infections caused by carbapenem-hydrolyzing oxacillinase-48 and Klebsiella pneumoniae carbapenamase-producing Enterobacteriaceae, but not for New Delhi metallo-β-lactamase producers. Gastrointestinal screening may permit early identification of patients with CRE infections. There is not enough evidence to recommend selective digestive decontamination for CRE carriers. Summary: The information for rapid diagnosis of CRE is accumulating. There are new agents with high in-vitro activity against CRE, but clinical experience is limited to case reports. Active surveillance with a high rate of compliance to basic infection control precautions seems to be the best approach to reduce the impact of CRE on vulnerable patients.